On fusion of range and intensity information using Graph-Cut for planar patch segmentation. (20th November 2008) - Kahler, Olaf; Rodner, Erik; Denzler, Joachim
Planar patch detection aims at simplifying data from 3D imaging sensors to a more compact scene description. We propose a fusion of intensity and depth information using Graph-Cut methods for this problem. Different known algorithms are additionally evaluated on low-resolution high-frame rate image sequences and used as an initialisation for the Graph-Cut approach. In experiments, we show a significant improvement of the detected patch boundaries after the refinement with our method.